Venom yield and its relationship with body size and fang separation of pit vipers from Argentina - de Roodt, Adolfo R. (2016)
Fil: de Roodt, Adolfo R. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Producción de Biológicos; Argentina.